Unity or multiplicity of psychology. Reflections on contemporary depth psychology - Dudek, Zenon Waldemar (Studia Psychologica: Theoria et praxis, 2004)
One of the basic questions in modern psychology is the problem of integration – in theory and practice. Many of the differences between concepts and views are basically reflection of the history. A part of the history is depth psychology (ideas of Freud, Jung, Adler, Fromm etc.). A Polish psychologist, J.Kozielecki, has presented the opinion, that on the way to integration of psychology there are two characteristic tendencies: the eclectic (openness to diversity of points) and the classical one (search for one new “integrated” psychology). The example of original and contemporary depth psychology (psychoanalysis, individual and analytical psychology, neopsychoanalysis, postjungians etc.) reflects as well the eclectic as the classical tendency. Freud has not accepted the proposal of eminent psychiatrist, E. Bleuler, to form wide psychological school based on the psychoanalytical concept of unconsciousness (termed “depth psychology”), so the result is multiplicity of Freudian schools and many divorces from original freudism. Other aspect of integration in psychology is assimilation of the psychoanalytical concepts in the “academic” psychology. There are some psychologist in Poland, psychotherapists and psychiatrists, which have presented the diversity of depth psychology as proposal for general psychology (i.e. A. Kępiński, A. Jakubik). For now we have to accept the fact, that the modern psychology (as theory and practice) is influenced by the tendency to integration (eclectic) and tendency to build it from beginnings as a relatively unite science (classical).